Control engineering perspective of fermentation process from zymomonas mobilis: Modeling, state estimation and control - Quintero Montoya, Olga Lucía (2009)
This work presents a control engineering perspective of ethanol production from biomass. The bacterium Zymomonas mobilis represents an important microorganism used for this purpose but it makes the fermentation process presents high nonlinearities. Last years this continuous fermentation process has been studied and several state estimation and linear and nonlinear control tools have been developed.